Flowers and climate change: a metabolic perspective. Issue 4 (1st July 2019) - Borghi, Monica; Perez de Souza, Leonardo; Yoshida, Takuya; Fernie, Alisdair R.
Summary: Adverse climatic conditions at the time of flowering severely hinder crop yields and threaten the interactions between plants and their pollinators. These features depend on a common trait: the metabolism of flowers. In this Viewpoint article, we aim to provide insight into the metabolic changes that occur in flowers in response to changes in climate and emphasize that these changes severely impact the fitness of autogamous and allogamous species, plant–pollinator interactions, and overall ecosystem health. We review the biochemical processes that lead to failure of gamete development and to alterations of color, scent and nectar secretion. Then, making use of open access expression data, we examine the expression of genes that may drive these changes in response to heat and drought. Finally, we present measurements of metabolites from flowers exposed to a heat wave and discuss how the results of this short‐term experiment may give rise to misleading conclusions regarding the positive effect of heat on flower fitness. We hope this article draws attention to this often‐neglected dynamic and its important consequences.